Enabling University : Impairment, (Dis)ability and Social Justice in Higher Education - Brabazon, Tara (SpringerBriefs in Education,, 2015)
This work takes the most recent, interdisciplinary research and demonstrates how to make higher education institutions open, accessible and socially just for staff and students with disabilities. Combining the scholarly fields of media platform management, information literacy, internet studies, mobility studies and disability studies, this book offers a guide and method to consider how students and staff with differing needs move through university processes, spaces and interfaces. It captures the challenges and potentials of both the online and offline university. The key concept of the book is universal design. This term and theory is used to move beyond the medical and social model of disability that disconnect and separate the issues of disability and impairment from core societal concerns. This book confirms that most of us will be touched by impairment through our lives. When matched with the necessity to retrain and gain new skills for a post-recession future, there must be a renewed commitment to not only the widening participation agenda of higher education, but also the enabling of universities for men and women with impairments.